The implantable loop recorder: A tool that is "here to stay". - Carel C. Cock (Indian Pacing and Electrophysiology Journal, 2002)
Syncope is a common clinical disorder accounting for 3 % for emergency room presentations and 1 % of hospital admissions 1. Moreover it has not always a benign course, with mortality rates up to 33 % at 1 year in patients with a structural cardiac disorders 2, 5. In addition costs for investigation for syncope is substantial and about 25 % of all patients remain undiagnosed 6. Investigation of patients with recurrent unexplained syncope may include electrocardiography and treadmill exercise testing, neurologic testing, tilt table testing, ambulatory Holter monitoring and electrophysiological testing. This review will briefly discuss these current available strategies and focus on the usefulness of a recently introduced tool using an implantable loop recorder (ILR) in the treatment of patients with a recurrent unexplained syncope.